Reconstructing Public Procurement Law in Indonesia: Toward a Framework of Good Governance and Legal Accountability - Fadila, Elviana Risqa Nur; Syafa’, Nadhifa Salsabilla; Fazila, Arina Nur; Wanda , Zakaria Nuriman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Public procurement represents one of the most strategic yet complex aspects of public governance, functioning as a critical instrument for achieving efficiency, accountability, and public welfare. In Indonesia, however, the legal framework governing procurement remains fragmented, being primarily regulated by presidential regulations rather than a parliamentary statute. This condition creates ambiguity in legal hierarchy and weakens institutional accountability, undermining the constitutional principle of negara hukum—a state based on law. Employing a normative-juridical method with comparative and philosophical approaches, this research analyses the structural and conceptual deficiencies within Indonesia’s procurement regulation, juxtaposed with best practices from jurisdictions such as the United Kingdom, South Korea, and Chile. The findings reveal that reliance on executive decrees has produced instability, limited judicial review, and excessive criminalisation of administrative errors, all of which hinder effective governance. Comparative evidence demonstrates that codification, transparency by design, and data-driven oversight strengthen both efficiency and integrity in public spending. Philosophically, the study argues that procurement reform is not only a matter of legal technique but also an ethical duty to realise justice, proportionality, and the public good. The paper concludes that Indonesia requires a codified Procurement Law enacted by Parliament to restore normative coherence, uphold accountability, and align its public procurement governance with constitutional and international standards.